Nyelvében él a kor - Koutny, Ilona (Investigationes Linguisticae, 2023)
The vocabulary of a language is constantly evolving, with new elements appearing and others passing out of usage, so it can reveal a lot about the time period in which it is studied as well as the worldview of its users. Through a study of Hungarian language usage, including words and expressions, some of the characteristics of the socialist era, the period after the regime change and of recent years can be illuminated. A comparison of them as well, as a comparison between an Internet survey of 10 years ago and a more recent one shows the changes in political, social, economic and cultural life, the multiplication of problems and the gloomy mood in Hungary.